External monetary shocks and monetary integration: Evidence from the Bulgarian currency board - Alexandru Minea; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2011)
Starting July the 1st 1997, Bulgaria adopted a Currency Board (CB) monetary system. This paper aims at investigating if the adoption of the CB monetary system, which involves the cost of loosing monetary autonomy, has provided a relatively better (with respect to other CEEC) monetary integration of Bulgaria with the European Monetary Union (EMU). Since Bulgarian monetary variables are endogenous under a CB, we focus on the ECB and FED interest rates as the main sources on monetary volatility. First, we find that ECB shocks are more rapidly absorbed and have less significant impact of domestic variables, with respect to other external monetary shocks (FED rate changes). Second, the responses of Bulgarian variables following changes in the ECB interest rate present lower persistence and significance, with respect to what the previous literature emphasized for other CEEC with monetary autonomy. This latter result still holds when accounting for different sources of cross-country heterogeneity outlined in the literature, thus supporting that the adoption of the CB may have worked as a rather good device in terms of integration of Bulgaria into the EMU.
Keywords: E42; E52; 330; Currency Board; Bulgaria; monetary shocks; ECB interest rate; FED interest rate; Currency Board; Zins; Schock; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Wirtschaftliche Anpassung; Bulgarien; USA